Atribusi Perilaku Atas Tudingan Materialistis Dalam Pernikahan Artis Bunga Zainal-Sukhdev Sing - Ria Rianggantara Rizqi Putra Paningkat (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This study explores the dynamics of attribution behavior in the context of celebrity marriages, focusing on the case of Bunga Zainal and Sukhdev Singh. The purpose of the research is to provide a more comprehensive and in-depth understanding of how attribution theory analysis can be applied to understand celebrity marriages that may be considered controversial. The research method used is qualitative, utilizing Harold Kelley's attribution theory approach, through primary data analysis from interviews across various podcast channels and secondary data from literature and online media reporting. The findings suggest that when consensus and distinctiveness are high, but consistency is low, behavior tends to be attributed to external or situational factors, namely the characteristics of Sukhdev Singh, rather than solely to materialistic motives. This indicates that Bunga Zainal's marriage is seen as a unique decision that is inconsistent with her previous behavior, yet similar to that of other celebrities in similar situations. This study highlights the importance of public understanding of attribution dynamics in influencing their views on specific events. In the context of communication studies, the research underscores the importance of considering attribution in media analysis and public responses to social issues and news.